Active but inoperable thrombin is accumulated in a plasma protein layer surrounding Streptococcus pyogenes - Naudin, Clément; Hurley, Sinead M.; Malmström, Erik; Plug, Tom; Shannon, Oonagh; Meijers, Joost C.M.; Mörgelin, Matthias; Björck, Lars; Herwald, Heiko (Thrombosis and Haemostasis, 2015)
Activation of thrombin is a critical determinant in many physiological and pathological processes including haemostasis and inflammation. Under physiological conditions many of these functions are involved in wound healing or eradication of an invading pathogen. However, when activated systemically, thrombin can contribute to severe and life-threatening conditions by causing complications such as multiple multi-organ failure and disseminated intravascular coagulation. In the present study we investigated how the activity of thrombin is modulated when it is bound to the surface of Streptococcus pyogenes. Our data show that S. pyogenes bacteria become covered with a proteinaceous layer when incubated with human plasma, and that thrombin is a constituent of this layer. Though the coagulation factor is found attached to the bacteria with a functional active site, thrombin has lost its capacity to interact with its natural substrates and inhibitors. Thus, the interaction of bacteria with human plasma renders thrombin completely inoperable at the streptococcal surface. This could represent a host defense mechanism to avoid systemic activation of coagulation which could be otherwise induced when bacteria enter the circulation and cause systemic infection.
Keywords: Thrombin; fibrinogen; proteolysis; coagulation; Streptococcus pyogenes